Pelaksanaan Pembagian Harta Warisan Berdasarkan Hukum Adat Pada Masyarakat Suku Minangkabau Di Kota Matsum II Medan - Huma Sarah; Zaini Munawir; Sri Hidayani (JUNCTO: Jurnal Ilmiah Hukum, 2021)
Indonesia has diverse customs, one of which is the Minangkabau tribe. Many Minang tribes go abroad to big cities that aim to change their destiny. The custom of the Minangkabau tribe is regulated according to the mother law (matrilineal). Over time the adat experienced a shift, especially in terms of the distribution of inheritance, especially the people of Bukittinggi, West Sumatra, who migrated or left their hometowns to Matsum II City, where the community had 80% inhabitants inhabited by the Minang tribe community. This raises the interest of writers to find out what is the cause of the shift in customs occur. The research method used is to come directly to the field and conduct interviews by taking a sample of 10 people, the sample was randomly selected by the criteria of the people who have Minangkabau ethnicity. Based on the results of the author's research conducted in the City of Matsum II, Medan Area District, 90% actually no longer use the customary inheritance system in the distribution of inheritance. The factors causing changes in the inheritance distribution system is due to the migration of the Minangkabau tribe community who have assets based on the results of the livelihood with their husband and wife while they are overseas so that the Minangkabau tribal people prefer the distribution of inheritance based on Islamic law.